Centrifugal Shape Sorting and Optical Response of Polyhedral Gold Nanoparticles. (21st June 2013) - Shin, Yu Jin; Ringe, Emilie; Personick, Michelle L.; Cardinal, M. Fernanda; Mirkin, Chad A.; Marks, Laurence D.; Van Duyne, Richard P.; Hersam, Mark C.
<x xml:space="preserve">Abstract</x> A centrifugal route for separating small 110‐faceted gold nanostructures, namely rhombic dodecahedra (RD) and triangular bipyramids (BPs), which form simultaneously during synthesis and cannot be separated by means of conventional filtration methods, is presented. The centrifuged solution shows two distinct bands: i) RD and ii) BPs, as verified in the corresponding scanning electron microscopy images. The sorted BPs show a refractive index dependence 2.5 times that of the as‐synthesized, unsorted mixture. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>